PEMBELAJARAN MAKE A MATCH BERBANTUAN VIDEO PEMBELAJARAN DENGAN KURIKULUM INTEGRATED DI MASA PANDEMI - Yeni Yuliana; Ruhban Masykur; Novian Riskiana Dewi (Universitas Majalengka, 2021)
The purpose of this study was to analyze the renewal of the integrated curriculum during the Covid-19 pandemic. The Covid-19 outbreak has had a major impact on various sectors, one of which is education. The world of education also feels the impact. As a teacher, it is necessary to create learning that can support the state of the world of education which is currently being carried out during the Covid-19 pandemic. From the renewal of the curriculum, the Cooperative Make a Match is applied, assisted by learning videos, which can improve students' understanding of mathematical concepts. Learning Make A Match is a learning model that can help students be more confident in solving a problem and with the help of learning videos of students in understanding learning material from far away without having to meet face to face with teachers in accordance with the rules of education during the Covid pandemic. -19. Based on the results of the treatment research analysis using the Make A Match cooperative learning model assisted by video learning in the experimental class is better than the conventional learning model in the control class.